Perkembangan Pembaharuan di Kerajaan Turki Usmani Abad ke XIX-XX - Khoiri, Miftahul; -, Sahri; -, Mizuar (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2023)
The longest-lived Islamic kingdom in the past was the Ottoman Empire. During its development, this kingdom experienced renewal within it which occurred in the 19-20 century AD. This article study describes the Ottoman Empire through the development of renewal within it. This article study uses historical methods, namely, heuristics, criticism, interpretation, and historiography using a multidimensional approach. As a result, it is said that reform in the Ottoman Empire took a long road. The defeat after defeat suffered by the Ottoman Empire in its wars had moved the hearts of the Sultans to carry out reforms in various fields. In its development, there were three streams of reform, namely Western, Islamic and Nationalist. The Western school says that the decline of the Ottoman Empire was caused by the Sharia which controlled all aspects of life in the Ottoman Empire. The view of the Islamic sect is that religion has never been an obstacle to progress, Turkey has actually gone backwards because it does not implement Islamic law. The Nationalist sect believes that Turkey's decline was caused by the reluctance of Muslims who did not accommodate changes.